2019
DOI: 10.1101/554477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limits to environmental masking of genetic quality in sexual signals

Abstract: There is considerable debate over the value of male sexual ornaments as signals of genetic quality. Studies alternately report that environmental variation enhances or diminishes the genetic signal, or leads to crossover where genotypes perform well in one environment but poorly in another. A unified understanding is lacking. We conduct the first experimental test examining the dual effects of distinct low and high genetic quality (inbred versus crossed parental lines) and low, through high, to extreme environ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…However, when the whole population experiences a reduction in the resources available for reproduction, whether the opportunity for selection increases will largely depend on the effect of resources on the variance in the expression of sexually selected traits, rather than on their mean (Arbuthnott & Whitlock ; Fox et al ). With a few notable exceptions (David et al ; Howie et al ), studies that test for condition dependence in sexually selected traits tend to focus on trait means rather than variances (Jennions et al ; Cotton et al ). Our study reveals remarkable concordance between the effects of resource limitation on specific trait means and variances (reduction in mean, increase in variance) and concomitantly the opportunity, relative importance, and patterns of pre‐ and postcopulatory sexual selection, which together point to patterns of heightened directional selection on condition‐dependent traits under dietary stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the whole population experiences a reduction in the resources available for reproduction, whether the opportunity for selection increases will largely depend on the effect of resources on the variance in the expression of sexually selected traits, rather than on their mean (Arbuthnott & Whitlock ; Fox et al ). With a few notable exceptions (David et al ; Howie et al ), studies that test for condition dependence in sexually selected traits tend to focus on trait means rather than variances (Jennions et al ; Cotton et al ). Our study reveals remarkable concordance between the effects of resource limitation on specific trait means and variances (reduction in mean, increase in variance) and concomitantly the opportunity, relative importance, and patterns of pre‐ and postcopulatory sexual selection, which together point to patterns of heightened directional selection on condition‐dependent traits under dietary stress.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this effect could potentially be reversed if female mating rate is lower under harsh environmental conditions, thus reducing the scope for competition to continue after mating and possibly increasing selection on precopulatory traits (Perry et al ). Furthermore, the opportunity for sexual selection will depend on the effect of resource availability on the variance in male sexually selected traits, rather than on their mean, yet we know little about how environmental conditions influence variances in sexually selected traits (David et al ; Howie et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it may be possible to detect and select on genetic quality under controlled conditions in the laboratory (Bellamy et al, 2014;Dugand et al, 2018Dugand et al, , 2019, genetic variation in fitness-related traits, including sexual signals, may often be obscured in natural environments where individuals develop under a wide range of conditions such as nutrient abundance. For example, Howie et al (2019) observed the predicted effects of genetic quality on eye-stalk width when flies were reared on an intermediate-quality larval diet, but not when flies were reared on lower-or higher-quality diets.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have directly compared the roles of environmental, genetic and G × E variation in the expression of condition‐dependent traits (although see de Boer et al, 2018; Bonduriansky et al, 2015; Cotton et al, 2004; Howie et al, 2019; Vega‐Trejo et al, 2018). A recent study on Drosophila melanogaster reported that the environmental component of condition (larval diet quality) was larger and more consistent than the genetic component (mutation load) and that some traits responded to environmental quality only (Bonduriansky et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation